Familiar violence a history of child abuse - Montgomery, Heather (Heather Kate) (Cambridge, United Kingdom Polity Press, 2024)
"Child abuse casts a long shadow over the history of childhood. Across the centuries there are numerous accounts of children being beaten, neglected, sexually assaulted, or even killed by those closest to them. This book explores this darker side of childhood history, looking at what constituted cruelty towards children in the past and at the social responses towards it. Focusing primarily on England, it is a history of violence against children in their own homes, covering a large timeframe which extends from medieval times to the present. -- Undeniably, the experience of children in the past was often brutal, and children were treated with, what seems to contemporary mores, callousness, and cruelty. However, historians have paid far less attention to how the mistreatment of children was understood within its contemporary context. Most parents, both now and in the past, loved their children and there have always been widely shared understandings of the boundaries that separate the acceptable treatment of children from the intolerable and morally wrong. This book will examine how these boundaries have changed and been contested over time and, in doing so, provides a context to the many forms of violence experienced by children in the past." -- From publisher's website.
Introduction: Personal reflections and disciplinary perspectives -- Infanticide -- Abandonment, parish nursing , and baby farmers -- Neglect -- Discipline, socialization and physical abuse -- Incest and child secual abuse in the home -- Intervening, prosecuting and preventing abuse -- The rise and fall of child abuse experts -- Conclusions: Child abuse now and in the future.
Includes bibliographical references (pages 185-206) and index.
Keywords: Children and violence; Child abuse -- England -- History; Child abuse -- England -- Social aspects; Family violence -- England -- History